A comparison of recreational skiing- and snowboarding-related injuries at a Colorado ski resort, 2012/13-2016/17. Issue 3 (2nd July 2020) - Pierpoint, Lauren A.; Kerr, Zachary Y.; Crume, Tessa L.; Grunwald, Gary K.; Comstock, R. Dawn; Selenke, Darcy K.; Khodaee, Morteza
ABSTRACT: The purpose of this study was to compare injury patterns between recreational skiers and snowboarders. Injured skiers (n = 3, 961) and snowboarders (n = 2, 428) presented to a mountainside medical clinic, 2012/13-2016/17. Variables investigated for analysis included demographics/characteristics, injury event information, and injury information. Skiers were older than snowboarders (34.3 ± 19.3 vs. 23.2 ± 10.5 years, p < 0.001); a greater proportion of skiers were female (46.3% vs. 27.8%, p < 0.001). Most skiers (84.4%) and snowboarders (84.5%) were helmeted at the time of injury (p = 0.93). Snowboarders were most frequently beginners (38.9%), skiers were intermediates (37.8%). Falls to snow (skiers = 72.3%, snowboarders = 84.8%) and collisions with natural objects (skiers = 9.7%, snowboarders = 7.4%) were common injury mechanisms. Common skiing injuries were knee sprains (20.5%) and head trauma (8.9%); common snowboarding injuries were wrist fractures (25.7%), shoulder separations (9.1%), and head trauma (9.0%). Given that injury patterns significantly differ between sports, it is important for clinicians, ski patrollers, and resorts to develop and deliver sport-specific injury prevention interventions to most effectively decrease injury burden.